2018
DOI: 10.1140/epjc/s10052-018-6438-0
|View full text |Cite
|
Sign up to set email alerts
|

Helicity amplitudes in $$B \rightarrow D^{*} \bar{\nu } l$$ B → D ∗ ν ¯ l decay

Abstract: We use a recent formalism of the weak hadronic reactions that maps the transition matrix elements at the quark level into hadronic matrix elements, evaluated with an elaborate angular momentum algebra that allows finally to write the weak matrix elements in terms of easy analytical formulas. In particular they appear explicitly for the different spin third components of the vector mesons involved. We extend the formalism to a general case, with the operator γ μ −αγ μ γ 5 , that can accommodate different models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 60 publications
4
40
0
Order By: Relevance
“…So far, several studies have been devoted to exploring the activity and products of GLY electro-oxidation over the catalysts. [17][18][19][20][21][22] Pt is widely studied for GLY electro-oxidation both in acidic and alkaline media. It has been reported that GLY electro-oxidation in acidic solutions is slower than that in alkaline solutions due to the sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, several studies have been devoted to exploring the activity and products of GLY electro-oxidation over the catalysts. [17][18][19][20][21][22] Pt is widely studied for GLY electro-oxidation both in acidic and alkaline media. It has been reported that GLY electro-oxidation in acidic solutions is slower than that in alkaline solutions due to the sluggish kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dai et al studied selective oxidation of GLY over an AuPt catalyst which showed a selectivity of 70 % for lactic acid. [21] Kim et al reported ternary PtRuSn/C catalysts which possessed high current densities and low onset potentials. The superior activity of the PtRuSn/C catalysts was attributed to the synergistic effects of Ru, Sn and Pt, which could facilitate the complete oxidation of CO or CO-like poisonous species.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of Co can be observed from the Co 2p XPS spectra on CuCo and CuCo-650. However, it should be noticed that the surface enrichment of Cu through surface segregation is induced by heat treatment, because the surface energy of Cu is lower than that of Co. [4,25] Consequently, the Co concentration on the surface of CuCo-650-400 is too low to be detected by XPS, although the EDS mapping demonstrates the existence of Co in CuCo-650-400. Meanwhile, the ratio of Cu and Co of CuCo-650-400 is measured to be ≈50:1 by inductively coupled plasma mass spectrometry.…”
Section: Co 2 Reductionmentioning
confidence: 99%
“…DOI: 10.1002/smtd.201900362 of renewable energies, [1][2][3][4][5][6] carbon dioxide sequestration and capture, [7][8][9] to electrochemical, [10][11][12] photo and photoelectrochemical techniques, [13][14][15] etc., have been explored to reduce carbon dioxide. These processes would be of particular interest if value-added products could be produced during the reduction of carbon dioxide.…”
mentioning
confidence: 99%
“…Combining two or three of the red, green, and blue (RGB) emission is a typical strategy to produce multicolor, especially for white light generation . However, heterogeneous structures set up by spatial assembly of building blocks with individual RGB emissions are usually bulky, inefficient, complicated, and costly . Although various materials including semiconductors, quantum dots, optical or nonlinear optical crystals, and organic dyes have been applied to generate RGB emission simultaneously, the available multicolor sources based on a single material with monolithic structure are still limited.…”
Section: Introductionmentioning
confidence: 99%